Intercultural Communication and Values-Based Orientations of Youth: Social Mobility and Problems of Self-Realisation - Tolmacheva, Svetlana V.; Skok, Natalia I.; Fomichev, Igor Yu. (International Journal of Criminology and Sociology, 2022)
The ability to interact at the level of interpersonal communication allows to say that young people not only perceive society as an environment for their self-realisation, but also use it to gain new experience, that can determine the development of an individual. The relevance of the study is determined by the fact that each act of communication must be implemented for the purposes of development under certain conditions that affect not only the communication environment itself, but also other forms of interaction at the level of the individual, communality or community. The novelty of the subject matter is determined by the fact that the formation of intercultural communication is possible only if programs of social mobility and, accordingly, cultural exchange are implemented. The authors show that such progress is most likely to be achieved in the external environment, which is determined by the presence of external influences. The authors of the paper primarily refer to this effect as the environment of an educational institution. The leading research method is a sociological survey and the method of analysis, which make it possible to comprehensively consider the value priorities and preferences that are characteristic of modern student youth. The practical significance of the study is determined by structuring and factor analysis, which allows to distribute the cultural layer into various social groups and ensure youth intercultural exchange both in the context of local student communication and in the context of an increase in the level of academic mobility.